Against the Current: Art and Resistance on the Banks of the Santa Maria da Vitória River - Gandini, Marcelo; Dala, Jovani (Farol, 2025)
This essay proposes a reflection on how changes in riverside landscapes influence the visual artist’s imagination, based on a sensitive journey along the Santa Maria da Vitória River (ES). The analysis is anchored in the aesthetic experience and artistic production of Marcelo Gandini and Jovani Dala, whose works emerge as forms of symbolic resistance to territorial transformations. Drawing on authors such as Tuan (2012) and Maderuelo (2006), we discuss how art can reaffirm memory and affection for lived places, operating as an ethical, poetic, and political gesture.